Non-native Minnows Threaten Quillwort Populations in High Mountain Shallow Lakes - Gacia, Esperança; Buchaca, Teresa; Bernal-Mendoza, Nayeli; Sabás, Ibor; Ballesteros, Enric; Ventura, Marc (Frontiers in Plant Science, 2018)
Submersed aquatic plants are a key component of shallow, clear water lakes contributing to primary production and water quality. High mountain lakes are naturally fishless although invasive trout and most recently minnows have been introduced causing a major impact on fauna richness. The Pyrenean high mountain range has preserved soft-water oligotrophic boreal isoetids in their southern limit of distribution but the recent fish introduction is a potential factor of stress that needs to be addressed. We here work under the hypothesis that due to contrasting ecological features, trout will not be heavily affecting quillwort populations while minnows will have a strong effect on zooplankton and small zoobenthos that will promote algal growth and reduce light availability for the underwater meadows. Ten Pyrenean shallow lakes representative of three scenarios -fishless, with trout and with minnows-, were sampled for meadow structure, water column and benthic environment characterization in mid summer 2015 and 2016. Quillwort biomass allocation (above vs. belowground), epiphytic load, and composition of the algal community (abundant cyanobacteria) differed in the presence of minnows. In trout lakes biomass allocation and epiphytic load were average and the algal community composed by chlorophytes and diatoms as in fishless lakes. Biomass ratio was close to thresholds of negative buoyancy in minnow lakes indicating that meadows were at risk of uprooting and consequent de-vegetation. Total and soluble carbohydrates were lower and the sporangia contained significantly less reserves to constrain growth and expansion in the presence of minnows. Lake scenarios were coupled to physicochemical differences with low light, high phosphorus and Chl-a (mesotrophia) in minnow lakes, while trout and fishless lakes remained oligotrophic. This is the first study assessing the impact of non-native fish on soft-water isoetids from mountain lakes and shows that minnows are a major threat to quillworts. The impaired light environment (from epiphytic algal overgrow and water column Chl-a) entails consequent regression (i.e. no recruitment) and de-vegetation (uprooting) of the meadows. Since soft-water oligotrophic mountain lakes are protected under the Habitats Directive, some action needs to be urgently implemented not only to preserve quillworts but to the overall ecological integrity of the lakes.